2009
DOI: 10.1007/s00586-009-1036-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cage positioning and cage type on cage migration and fusion rates in patients with monosegmental posterior lumbar interbody fusion and posterior fixation

Abstract: In posterior lumbar interbody fusion, cage migrations and lower fusion rates compared to autologous bone graft used in the anterior lumbar interbody fusion procedure are documented. Anatomical and biomechanical data have shown that the cage positioning and cage type seem to play an important role. Therefore, the aim of the present study was to evaluate the impact of cage positioning and cage type on cage migration and fusion. We created a grid system for the endplates to analyze different cage positions. To an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 22 publications
5
70
1
3
Order By: Relevance
“…The initial advice for transforaminal lumbar interbody fusion (TLIF) was to place the intervertebral cage in the middle/posterior third of the disc space [25]. Posterolateral placement within the intervertebral space, where the endplate is thicker [8] and stronger [8,26], has been suggested following a biomechanical study assessing the risk of cage subsidence [14], whereas central placement has shown greater subsidence in a clinical study [15]. With regard to anterior placement, both a cadaveric [27] and a clinical study [28] involving TLIF found no difference in intervertebral lordosis when cages were placed in the anterior half of the disc space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial advice for transforaminal lumbar interbody fusion (TLIF) was to place the intervertebral cage in the middle/posterior third of the disc space [25]. Posterolateral placement within the intervertebral space, where the endplate is thicker [8] and stronger [8,26], has been suggested following a biomechanical study assessing the risk of cage subsidence [14], whereas central placement has shown greater subsidence in a clinical study [15]. With regard to anterior placement, both a cadaveric [27] and a clinical study [28] involving TLIF found no difference in intervertebral lordosis when cages were placed in the anterior half of the disc space.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to cage shape, it has been shown that lordotic 'wedged' cages or structural allograft results in greater monosegmental lordosis than non-wedged cages [15,[32][33][34][35]. However, the effect of other cage parameters such as cage height and length has not been previously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relatively smaller contact area between the defective superior endplate of the L5 vertebra and the banana-shaped cage might influence the anterior dislodgement of the cage. Even though there have been some experimental studies that the cage shapes do not affect construct stability4,10,16), cage migration could be affected by cage type and positioning1). Therefore, a different type of cage from the banana-shaped ones could have been better for the patient in this particular case.…”
Section: Discussionmentioning
confidence: 91%
“…Clinically symptomatic cage migration into the endplates or spinal canal is a devastating cause of failed back surgery. 1 When lumbar cage subsidence occurs there are many concerns about recurrence of foraminal stenosis and sagittal malalignement. 18 Cage retropulsion leads to compression of the neural structures with progressive back pain and sciatica.…”
Section: Discussionmentioning
confidence: 99%